THE CHALLENGES OF OPERATIONS CONTROL CENTRES (OCC) IN EUROPEAN BUSINESS AVIATION (Perner's Contacts, 2013)
Operations control centre (OCC) is a very important unit in the structure of every operator. The dispatchers’ scope of tasks may be very large depending on the type of operation as well as size of the company. In business aviation the OCC often has an even more specific role and right training and activities selection are crucial to run the OCC. This article´s aim is to describe tasks and training of OCC personnel in the light of the current European legislation.